High Neutrophil-to-Albumin Ratio Predicts Postoperative Pneumonia in Aneurysmal Subarachnoid Hemorrhage - Zhang, Xin; Zhang, Sheng; Wang, Congkai; Liu, Ran; Li, Aimin (Frontiers in Neurology, 2022)
Background and Aim There is still an absence of objective and easily accessible biomarkers despite the variety of risk factors associated with postoperative pneumonia (POP) in patients with aneurysmal subarachnoid hemorrhage (aSAH). In the present study, we have thus evaluated the relationship between the neutrophil-to-albumin ratio (NAR) and POP in patients with aSAH. Methods Several consecutive patients (n = 395) who had undergone clipping or coiling of the aneurism were retrospectively assessed, of which we were able to analyze the existing population data and the related baseline variables. The patients were divided into POP and revealed not to occur. To identify independent predictors, we used the recipient operation feature (receiver operating characteristic, ROC) curve and a logic regression analysis. Results This cohort was based on POP that occurred in 78 out of the 395 patients (19.7%), and these revealed a significantly higher NAR than those without (0.31 [0.25–0.39] vs. 0.23 [0.18–0.28]; p < 0.001). On the other hand, a multivariate logistic regression analysis showed that NAR (odds ratio = 1.907; 95% confidence interval, 1.232–2.953; p = 0.004) was independently associated with a POP after due adjustment for confounders. Moreover, the predictive performances of NAR for POP were also significant (area under the ROC curve [95% CI] 0.775 [0.717–0.832]; p < 0.001). Conclusion The elevation of NAR at admission in patients with aSAH might help predict POP.